Evaluation of an oral supplement containing Phyllanthus emblica fruit extracts, vitamin E, and carotenoids in vitiligo treatment. Issue 1 (6th October 2014) - Colucci, Roberta; Dragoni, Federica; Conti, Rossana; Pisaneschi, Lisa; Lazzeri, Linda; Moretti, Silvia
Abstract P hyllanthus emblica, vitamin E, and caroteinods are compounds showing antioxidative, anti‐inflammatory, and repigmenting effects, whose role in vitiligo treatment has not been evaluated so far. Sixty‐five subjects (group A) were treated with one tablet of an oral supplement containing P. emblica (100 mg), vitamin E (10 mg), and carotenoids (4.7 mg) three times/day for 6 months and compared with a control group (group B, 65 patients), which instead was not treated with antioxidants. Both groups were simultaneously treated with a comparable topical therapy and/or phototherapy. After a 6 months follow‐up, a significantly higher number of patients in group A had a mild repigmentation on the head/neck regions (p = 0.019) and on the trunk (trend, p = 0.051). The number of patients who presented no repigmentation in head/neck, trunk, upper, and lower limbs was significantly higher in group B (respectively, p = 0.009, p = 0.001, p = 0.001, p = 0.025). Moreover, group B patients showed higher signs of inflammation (p = 0.002), a more rapid growth of the lesions (p = 0.039), a higher percentage of worsening disease (p = 0.003), and more erythema (p = 0.059), whereas group A patients showed a higher percentage of steady disease (p = 0.065). Our results suggest that the supplement with antioxidants in patients with vitiligo might represent a valuable instrument to increase the effectiveness of other vitiligo treatments. [Correction added after online publication 06‐Oct‐2014: the dosages of vitamin E and carotenoids have been updated.]